Fundamentals of computation theory : 20th International Symposium, FCT 2015, Gdańsk, Poland, August 17-19, 2015, Proceedings /: 20th International Symposium, FCT 2015, Gdańsk, Poland, August 17-19, 2015, Proceedings. (2015) - Unknown
No abstract available